1970
DOI: 10.1128/jb.104.1.434-442.1970
|View full text |Cite
|
Sign up to set email alerts
|

Polyphasic Taxonomy of the Genus Vibrio: Polynucleotide Sequence Relationships Among Selected Vibrio Species

Abstract: Polynucleotide relationships among selected Vibrio species were examined by means of deoxyribonucleic acid (DNA) reassociation reactions and chromatography on hydroxyapatite. Relative levels of intraspecific DNA duplex formation (V. cholerae-V. cholerae and V. parahaemolyticus-V. parahaemolyticus) were found to be high at 60 C (>80%), and only minimally reduced at 75 C. Interspecific DNA duplexes between V. cholerae DNA and that of the non-cholera vibrios also exhibited high relative levels of formation at 60 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
23
1

Year Published

1971
1971
2004
2004

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(29 citation statements)
references
References 34 publications
5
23
1
Order By: Relevance
“…The reciprocal DNA homology experiments between isolates of V. parahaemolyticus and V. alginolyticus showed them to be 67% homologous to one another. These results sharply contrast with those of Citarella and Colwell, who in a similar study reported less than 10% homology between V. parahaemolyticus and V. alginolyticus (4). This discrepancy between Citarella and Colwellrs findings and those of our study is attributable to their use of distinctly different organisms as representative strains of V. alginolyticus.…”
contrasting
confidence: 99%
See 1 more Smart Citation
“…The reciprocal DNA homology experiments between isolates of V. parahaemolyticus and V. alginolyticus showed them to be 67% homologous to one another. These results sharply contrast with those of Citarella and Colwell, who in a similar study reported less than 10% homology between V. parahaemolyticus and V. alginolyticus (4). This discrepancy between Citarella and Colwellrs findings and those of our study is attributable to their use of distinctly different organisms as representative strains of V. alginolyticus.…”
contrasting
confidence: 99%
“…Sakazaki's original scheme (21) for the differentiation of V. parahaemolyticus from the related biotypes V. alginolyticus and V. anguillarum was based on the differential ability of these organisms to grow at various salt concentrations, to ferment various sugars, and to produce acetylmethylcarbinol. Subsequent investigations have shown that these tests are not adequate, as there are numerous marine vibrios whose identity remains ambiguous because they do not wholly resemble any one of the three biotypes DNA RELATIONSHIPS OF MARINE VIBRIOS Recent attempts to clarify the taxonomic position and relationships within the marine vibrio group have relied on determinative characterization, including Adansonian analysis and deoxyribonucleic acid (DNA)-DNA hybridization experiments as well as an amalgamation of these procedures (4,5,8,11,17). Hanaoka et al, using the DNA agar hybridization technique, determined the inter-and intraspecific relationships between selected strains of V. parahaemolyticus and V. cholerae (8).…”
mentioning
confidence: 99%
“…Only three of these strains hybridized with the group containing strains isolated from cases of gastroenteritis, pointing to the inadequacy of the traits used for the identification of this organism. The considerable DNA homology between strains of B. parahaemolytica and B. alginolytica observed by Anderson and Ordal (3) is in agreement with the in vitro DNA/DNA hybridization studies of Hanoaka et al (17) and contrary to the results obtained by Citarella and Colwell (12). As previously pointed out (3), the strains studied by the latter authors under the designation V. alginolvticus were not authentic strains of this species, differing from the type strain in the moles percent guanine plus cytosine contents of their DNA and in their phenotypic properties (12,13).…”
supporting
confidence: 88%
“…The considerable DNA homology between strains of B. parahaemolytica and B. alginolytica observed by Anderson and Ordal (3) is in agreement with the in vitro DNA/DNA hybridization studies of Hanoaka et al (17) and contrary to the results obtained by Citarella and Colwell (12). As previously pointed out (3), the strains studied by the latter authors under the designation V. alginolvticus were not authentic strains of this species, differing from the type strain in the moles percent guanine plus cytosine contents of their DNA and in their phenotypic properties (12,13). In addition, it should be mentioned that the studies of Colwell (13) and Citarella and Colwell (12) were primarily directed to the differentiation of B. parahaemolvtica and V. cholerae and did not address themselves to the more important problem of the relation of B. parahaemolvtica to other common marine bacteria.…”
supporting
confidence: 88%
“…Many have been placed in Vibrio (3,27,47,58), Aeromonas (36), Pseudomonas (10,42), and Beneckea (7,9). Determinations of the guanine plus cytosine (GC) content of the deoxyribonucleic acid (DNA) of these strains have shown that the moles % GC ranges from 39-48 (5,11,13,28,32). Some of these organisms are pathogenic for marine fish and shellfish (51).…”
mentioning
confidence: 99%